Factors That Influence Third-Trimester Pregnant Women in Choosing To Give Birth at Health Facilities in The Working Area of Public Health Centre Siak Hulu 2 Siak Hulu 2 District In 2023 - Heni Heriyeni; Zuliyana Zuliyana; Siska Indrayani; Rizki Natia Wiji (The International Science of Health Journal, 2023)
The maternal mortality rate is still relatively high, so it needs continuous effort between health service providers and patients to make birth decisions. As per the SDGs program, to reduce the risk of maternal death in childbirth, childbirth must be carried out by trained professional health workers and in health services. This study aimed to determine the factors that influence third-trimester pregnant women in choosing to give birth at health facilities in the working area of Public health Center Siak Hulu 2, Siak Hulu 2 District. The research design was a correlational descriptive study. The research was conducted on the active site of the Public health center Siak Hulu 2. The population in this study was 35 pregnant women. The sample in this study was 35 pregnant women using total sampling. Data analysis was done univariately, bivariate, using the Chi-Square statistical test. The results showed that there was a relationship between age and the choice of place of delivery in the Siak Hulu 2 Working Area, with a P-Value of 0.03, there was a relationship between parity and the choice of place of delivery with a value P-Value 0.01, and there is a relationship between distance and choice of area of delivery with a P-Value of 0.001. This study concludes that all factors related to the will of the place of delivery in third-trimester pregnant women have a relationship. Suggestions are expected for health workers to be able to provide more information to pregnant women that it is essential to give birth at a health facility.